ARKA IN PHASE OJL 7 GREAT BK MOVES: A PORTRAIT OF THE INITIAL SHIFT OF BK SERVICES FROM REACTIVE TO PARTICIPATORY - Putra Asga Elevri; Yadi Ruyadi; Encep Syarief Nurdin; Asep Dahliyana; Juntika Nurihsan; Ace Suryadi (SOSIOEDUKASI, 2026)
This article analyzes the application of the ARKA framework—Activities, Reflection, Conceptualization, and Application—in the on-the-job learning (OJL) phase of the 7 Great BK Jurus Program as a micro-pedagogical mechanism for guidance and counseling (BK) services. The focus of the article is directed at how the implementation of ARKA is represented in the PSKP report on the initial implementation of the 7 Great BK Skills and Guardian Teacher Program, as well as how these representations can be read as an early indication of the shift of BK services from a reactive approach to a more participatory service. This article uses a qualitative approach with a secondary document analysis design. The main source of analysis is the published PSKP report, supported by literature on BK services development, experiential learning, professional reflection, and program implementation. This article does not use raw data in the form of interview transcripts, FGDs, or internal field notes as a corpus of analysis. The results of the analysis show that ARKA can be understood as a service flow that connects activities, reflection, conceptualization, and application in BK practice. The PSKP report indicates that there are service practices that are more interactive, needs-based, reflective, and applicative, although these changes are still preliminary and uneven. Obstacles such as limited service time, infrastructure, monitoring, and legitimacy of regional facilitators continue to limit the sustainability of ARKA implementation. This article concludes that ARKA has the potential to strengthen BK development services if supported by the reflective capacity of implementers and school institutional support.